Comprehensive comparison of MR image quality between intratympanic and intravenous gadolinium injection using 3D real IR sequences. (3rd August 2019) - Li, Yang; Sha, Yan; Wang, Feng; Lu, Ping; Liu, Xilan; Sheng, Yaru; Zhang, Zhongshuai; Liu, Mengxiao
Abstract: Background: Intratympanic and intravenous gadolinium administration is used to visualise endolymphatic hydrops. Aims/objectives: The goal of this study was to compare the image quality between intratympanic (IT-method) and intravenous (IV-method) gadolinium administration using three-dimensional inversion recovery with real reconstruction (3D real IR) sequences. Materials and methods: A number of 152 patients with Meniere's disease were included. The 3D real IR sequence was performed 24 h after IT administration or 4 h after IV administration. The detection rate of endolymphatic hydrops, signal-to-noise ratio (SNR), and contrast-to-noise ratio (CNR) of the two methods were compared. Specifically, the average image scores of the two methods were evaluated by two radiologists. Results: The SNRROI and CNRs of the IT-method were higher than those of the IV-method, whereas no significant difference between the IT-method and IV-method with regard to the SNRB was found. The average image scores were 3.49 ± 0.12 and 3.30 ± 0.12 for the IT-method and IV-method, respectively ( p = .229). No statistically significant difference was found between two methods in terms of the detection rate of endolymphatic hydrops. Conclusions and significance: IT-method images can display endolymphatic hydrops more precisely than IV-method images. The IV-method can be used as an alternative to the IT-method in clinical applications to some extent.